Government Role of Urban Poor Community Empowerment Program in DKI Jakarta - Dalimunthe, Henny Herawaty Boru (Universitas Negeri Semarang, 2017)
This research based on the fact that there still be poor community in urban area, DKI Jakarta. The purpose of this research is giving a view of government role in giving environmental, social, ecomical, as well as educational help for the community. The result of the research shows that community empowerment program is coordinated by national team of poverty alleviation acceleration (TNP2K). Government institution such as social ministry, public work ministry, empowerment and family welfare movement, community and women empowerment institution and family planning, and DKI Jakarta community empowerment have environmental guidance, social, and economical empowerment program. The result of this research also shows that nonformal education guidance is needed to help poor society who have no chance to have education. The results of this research indeed conclude that the government has already had a role in the guidance of empowering urban poor commmunity in environmental, socal, and economical sectors but educational guidance to help empowerment process in the society is needed.